On two Jenynsia taxa (Cyprinodontiformes: Anablepidae) from Argentina, originally placed in the poeciliid genus Xiphophorus - Koerber, Stefan; de Las Mercedes Azpelicueta, María (Zootaxa, 2009)
The type material of Xiphophorus heckelii Weyenbergh, 1874 and X. obscurus Weyenbergh, 1877 has apparently been re-examined for the first time. Xiphophorus heckelii is confirmed as a junior synonym of Jenynsia multidentata (Jenyns, 1842). Xiphophorus obscurus is recognized as a senior synonym of Jenynsia pygogramma Boulenger, 1902, which is placed in synonymy. A lectotype and paralectotypes are designated for Jenynsia obscura (Weyenbergh, 1877).